2018
DOI: 10.1186/s40510-018-0208-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low level laser and low intensity pulsed ultrasound therapy on bone remodeling during orthodontic tooth movement in rats

Abstract: BackgroundQuality bone regeneration, which leads to the improvement of bone remodeling, is essential for orthodontic treatment. In order to improve bone regeneration and increase the amount of tooth movement, different techniques have been implemented. The object of this study is to compare the effects of low-level laser therapy (LLLT), low-intensity pulsed ultrasound (LIPUS), and their combination on bone remodeling during orthodontic tooth movement.MethodsEighty (80) male, 6-week-old Sprague Dawley rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 35 publications
2
25
0
1
Order By: Relevance
“…It was also reported that RANKL expression in a rat tooth movement model increased compared to the control group following lowpower laser irradiation. 25 The results of the present study were similar, with RANKL gene expression significantly higher in the 2.0 W group 24 hours after Nd: YAG laser irradiation. Our experiments also demonstrated that the RANKL/OPG ratio was higher than that of the control group 24 hours after laser irradiation.…”
Section: Discussionsupporting
confidence: 82%
“…It was also reported that RANKL expression in a rat tooth movement model increased compared to the control group following lowpower laser irradiation. 25 The results of the present study were similar, with RANKL gene expression significantly higher in the 2.0 W group 24 hours after Nd: YAG laser irradiation. Our experiments also demonstrated that the RANKL/OPG ratio was higher than that of the control group 24 hours after laser irradiation.…”
Section: Discussionsupporting
confidence: 82%
“…IL-1b expression was significantly higher in the 660 and 830 nm groups than in the control group on day 3, and the number of osteoclasts was significantly higher in the 660 and 830 nm groups than in the control group. This result indicates that 660 and 830 nm PBM can increase the expression of IL-1b to accelerate the rate of alveolar bone remodeling on the compression side, as reported in previous studies, 17,18 which also confirmed that PBM affects the proliferation and activation of some cells. [19][20][21][22] Especially, on days 3 and 5, the number of osteoclasts in the 660 nm group was higher than that in the 830 nm group, and the difference was statistically significant.…”
Section: Resultssupporting
confidence: 88%
“…LLLT incites vascularization of the bone defect, fracture position, as well as osteoblasts, which can assist the recuperation of hard tissue. 40 Several reports 41,42 have demonstrated that LLLT could accelerate tooth motion in animals. Some researchers used clinical trials to assess the effect of LLLT on the speed of OTM, but the findings were divergent.…”
Section: Discussionmentioning
confidence: 99%